Strategi Positioning Jasa Service Konter Samsung untuk Meningkatkan Volume Penjualan Smartphone di Klaten - Farida Puspita Harti (MAMEN: Jurnal Manajemen, 2025)
Humans are interconnected to obtain information and communication. Advanced communication produces sophisticated technology, called smartphones, loved by many people. The phenomenon of smartphone needs has resulted in the Samsung smartphone counter business, a promising and growing business branch in Indonesia. The main thing is the information needs of people who like to change smartphones, every year the business and its actors develop, increase in Indonesia. Marketing strategies, challenging positioning, so that competitors compete, until expected by the public. The purpose of the study, describe in depth, the positioning strategy of Samsung smartphone service, in order to increase Samsung smartphone sales at the Anugrah Samsung Smartphone counter, Klaten. The research method is descriptive, qualitative approach, field research type. The purpose of the study, direct understanding of real conditions and comparing Samsung smartphone repair services as a marketing medium, with positioning specifications. By knowing the price of Samsung smartphone repair services, it is expected that product sales can increase. The purposive sampling method, the informant selection. The criteria are owner; operator, one employee; three regular customers. The results of the study as a benchmark for the success of the positioning marketing strategy, with 4 indicators, can provide an increase in sales of Samsung smartphone products, namely: 1. target market with customer persona specifications from collecting ideal customer profile information, representing the target market of Samsung smartphone counters; 2. life cycle of Samsung smartphone counter service, its stages, introduction, providing new services that are not yet available to competitors; growth, expansion of services from business partners; maturity, decision making when market conditions are saturated; decline conditions, adaptation to technological changes and consumer preferences; 3. adding a diversification strategy, offering replacement for the selection of second hand Samsung smartphone/new Samsung smartphone sales services; 4. product differentiation, shaping consumer perceptions. In addition to Samsung product repair services, adding other smartphone product repair services is currently trending.